Hitelexpanzió, válság és válságkezelés a Horthy-korszakban - Schlett, András (Közép-Európai Közlemények, 2015)
This paper considers the reasons, the process and the results of external indebtedness in Hungary in the 1920s. We look at the importance of the League of Nations loans in the stabilization process and the relating currency sytem. We also look at the special characteristics of the excess amount of external loans and the resulting debates among economists and the intended government control. When the crisis broke out, the issue of the external debts became a red-hot economic issue of the country. At first the main goal of the crisis management was to save the country’s credit standing. However these measures caused further constriction of the real economy, because the empolyees with reduced wages and the mass of unemployed reduced the demand even more. At last the measures taken to find the way out, the exhaustion of the society and the economy, as well the political changes have achieved some pragmatical new elements.